Pengaruh Konflik Peran Ganda Dan Stres Kerja Terhadap Kinerja Polisi Wanita Di Polresta Yogyakarta - Titin Siswatiningsih; Nur Wening (Universitas PGRI Yogyakarta, 2021)
Working women at this time are very common, there are many considerations that encourage women to work where they have aspirations to have their own income, help their husbands meet their needs and there are also considerations for career actualization of their existence in the organization where they work. Female police, abbreviated as Polwan, are an example of working women. Policewomen are also bound by the same rules as male cops. A policewoman has two roles at once, in their homes as housewives and in their offices as career women. This research is an analysis of the effect of the dual role conflict (work-family, family-work) of policewomen and work stress (pressures on work) on their performance. Data collection was carried out using a questionnaire. Sampling using purposive sampling technique, namely married policewomen with a sample of 62 respondents drawn from as many as 75 policewomen who are married. Multiple role conflict is the first independent variable and job stress is the second independent variable, while Polwan's performance is the dependent variable. Based on the research results, the first independent variable (X1) and the second independent variable (X2) have an effect on the performance of female police officers (Y). This is evidenced by the value of the regression coefficient and the level of significance of each factor, namely -0.027 and 0.892; 0.698 and 0.008. The F-count is 10.047 with a significance level of 0.000, the adjusted R2 value is 0.229. Multiple role conflict has a significant negative effect on policewomen's performance, job stress has a significant positive effect on policewomen's performance.Keywords: Multiple Role Conflict, Job Stress and Employee Performance.